Security and Legal Protection for Building Owner of the Land Belongs to Others Related to Principle of Horizontal Separation - Rr. Dijan Widijowati; Aristyo Rahadiyan (International Journal of Science and Society, 2021)
The increasing need for land can lead to conflicts in the land sector; therefore, the Indonesian government has enacted Law Number 5 of 1960 concerning Basic Agrarian Principles, which intends to establish a National Agrarian Law based on Customary Law on land. The Land Law adopted by the Basic Agrarian Law rests on Customary Law which recognizes the horizontal scheiding principle. The implementation is with the existence of lease rights for buildings. In line with the principle of horizontal separation adhered to by the Basic Agrarian Law, building construction can be carried out either on one's land or on other people's land. The problem discussed in this study is how legal certainty and protection for building owners who stand on land owned by other people and what legal remedies the building owner can take to own the building still use other people's land. The research method used is normative juridical; typology used in this research is explanatory research and prescriptive research. The approach used in this research is normative. Based on this research results, Defendant I and Defendant II are not allowed to submit a petition for vacant buildings belonging to Plaintiff is on land owned by Defendant I and Defendant II. The building belonged to Plaintiff, so Defendant I and Defendant II did not have authority over the building. If it is related to the principle of horizontal separation, the request to vacate the establishment is contrary to the regulation adhered to by agrarian law in Indonesia. Can do another result of the efforts made by building owners to use other people's land through non-litigation, litigation, and abrasive actions.